The operation of innovation clusters in light of relationships in Hungary – qualitative research findings - Kovács, István (Wydawnictwo Uniwersytetu Ekonomicznego we Wrocławiu, 2019)
This paper discusses the operation of accredited innovation clusters in Hungary, applying qualitative methods. The focus of this research was to map the relations and cooperation within the clusters and their innovative effect. The aim of the study was to determine models and dimensions for revealing the intricate relationships by which we can describe them and by which they can be made measurable in the future. For this purpose, relationship marketing orientation, network competence, and proximity models that have already been presented in the international scientific literature were fitted to the cluster environment: the authors of this study interpret their dimensions in terms of the relations and cooperation within a cluster and examine their correlations with the cluster characteristics, as well as their impact on innovations
Argumenta Oeconomica, 2019, Nr 2 (43), s. 283-305
Keywords: cooperation; innovation clusters; market orientation; network competences; relationship marketing; relationship proximity